Program Strategy in Improving Road Quality: Strategi Program Dalam Meningkatkan Kualitas Jalan - Prabawati, Lia Andita; Mursyidah, Ilul (Indonesian Journal of Public Policy Review, 2020)
This study aims to determine the Sidoarjo Regency Government's Strategy in Improving Road Quality and to find out the Sidoarjo Regency Government's Strategic Constraints in Improving Road Quality. This study used qualitative research methods. The subjects in this study are Sub. General Affairs and Personnel Section, Implementing Computer Institutions, Road and Bridge Construction Section, and Head of Office. Technical Planning Field. Data collection techniques in this study were conducted through interviews, observation, and documentation. Then the data is processed using data analysis techniques using data collection, data reduction, data presentation, and drawing conclusions. The results of the research, it can be concluded that the strategy carried out by the Sidoarjo Regional Government uses a program strategy. Where program strategies are programs launched to help achieve the objectives of the strategy. As well as the constraints from the strategy that come from the internal and external sides, where the constraints from the internal side can come from the apparatus and institutions, while the external side comes from the environment, society, weather and so on.